Diphtheria: a re-emerging infectious disease - Suligavi, Shashidhar S.; Vishwanath, Divya K.; Gokale, Shilpa; Doddamani, S. S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Diphtheria is a fatal bacterial infection which affects the mucous membranes of oropharyngeal and nasal cavity, caused by aerobic gram-positive bacteria Corynebacterium diphtheriae. Clinical diphtheria is on the increase worldwide, mainly affecting developing countries and leading cause of morbidity and mortality. We sought to understand its presentation among patients and also early intervention of the disease. The objective of the study was to study the clinico-demographic profile of cases, the relationship between immunization status and clinical disease, the role of microbiological investigations and to identify complications in diphtheria cases. Methods: This study is a hospital based observational study from September 2019 - September 2020 at a tertiary care centre, S.Nijalingappa Medical College and HSK hospital, Bagalkot, Karnataka. The cases were analysed with respect to demographic details, clinical features, immunization status, microbiological confirmation and complications of diphtheria cases. Results: 32 cases were suspected to have diphtheria on clinical examination. The mean age of presentation was 15 years. Fever, sore throat, difficulty in swallowing, neck swelling and pseudomembrane in oral cavity were the common signs and symptoms. Airway compromise, myocarditis and neurological complications were noted. Antidiphtheritic serum (ADS) was tried in all 32 cases and 8 cases had adverse reactions. Case fatality rate was 12.5%. Conclusions: Shifting of occurrence of diphtheria in the age group of >5 years suggest the need to improve and strengthen the immunization program specially the booster doses.